Gut bacterial tyrosine decarboxylases restrict levels of levodopa in the treatment of Parkinson’s disease - Sebastiaan P. van Kessel (Nature Portfolio, 2019)
The gut microbiota can impact the bioavailability of therapeutic drugs. Here, the authors show that bacterial tyrosine decarboxylases (TDC) decrease the levels of levodopa, the primary treatment in Parkinson’s disease, by conversion to dopamine, and suggest TDC as a potential predictive biomarker for treatment.